Adherence to medication and characteristics of Japanese patients with non-valvular atrial fibrillation. Issue 3 (September 2017) - Suzuki, Tsuyoshi; Shiga, Tsuyoshi; Omori, Hisako; Tatsumi, Fujio; Nishimura, Katsuji; Hagiwara, Nobuhisa
Abstract: Background: Adherence to medication plays an important role in the prevention of morbidity and mortality in non-valvular atrial fibrillation (NVAF) patients. The aim of this study is to assess adherence to medication and risk factors for non-adherence in Japanese NVAF patients who are prescribed anticoagulants. Methods: A total of 378 outpatients with NVAF who completed self-reported questionnaires were analyzed in this prospective study (mean age 69 ± 12 years; 26% female). Self-reported adherence to cardiovascular drugs including anticoagulants was measured with a modified Siegal scale. Depression was defined as a Patient Health Questionnaire-9 score of ≥10. Univariate and multivariate analyses were performed on several variables to analyze factors affecting non-adherence. Results: In total, 291 (77%) of our patients received warfarin, and the remainder received direct oral anticoagulants. Fifty-two (14%) patients were defined as non-adherent. Univariate analyses showed that age <65 years, ≥2 times daily dosing of cardiovascular drugs and employment, but not depression, were significantly associated with non-adherence, 1.87 (95% CI: 1.01–3.42, p  = 0.04), 2.97 (95% CI: 1.64–5.49, p  < 0.01), 2.11 (95% CI: 1.16–3.93, p  = 0.01), and 0.74 (95% CI: 0.26–2.64), respectively. Multivariate analysis showed that only ≥2 times daily dosing was a significant independent risk factor (HR 3.06, 95% CI: 1.67–5.69, p  < 0.01). Conclusions: Our study showed that the prevalence of non-adherence to medications was 14% in NVAF patients. Frequent daily dosing was an independent risk factor for non-adherence to medication (UMIN-CTR No. UMIN 000023514).